PENGARUH CORPORATE GOVERNANCE, KUALITAS AUDIT DAN PERGANTIAN AUDITOR TERHADAP KONSERVATISME (Studi Empiris âMost Trusted Company Based On Corporate Governance Perception Indexâ di BEI Tahun 2007-2010) - Anindhita Ismawardani, 08.05.52.0085; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2013)
This studys aim is to examine and analyze the effect of corporate governance, audit quality and auditor turnover for the integrity of the financial statements in the